Analisis fenomena Kurva J di Indonesia - Lia Ika Lestari; Birgitta Dian Saraswati; Yustinus Wahyudi (Jurnal Ekonomi Modernisasi, 2022)
The free-floating exchange rate system in Indonesia has consequences for fluctuations in the Rupiah exchange rate. In accordance with the J-Curve theory, will the weakening of the Rupiah value have an impact on improving the trade balance in the long term or will it worsen the trade balance condition in the long term. This study will examine how the influence of the Rupiah exchange rate on the trade balance in both the short and long term and whether the J-Curve phenomenon occurs in Indonesia using the Vector Error Correction Model (VECM) analysis technique in the observation period 2015.1-2020.12. The results of this study prove that the J-Curve phenomenon occurs in the Indonesian economy. The findings show that the depreciation of the Rupiah in the short term will cause a trade balance deficit, but in the long term, the depreciation of the Rupiah will cause a trade balance surplus. The results of the variance decomposition show that the exchange rate has a major role in the formation of fluctuations in the trade balance. In addition, shocks that occur in the exchange rate will be responded to by movements in the trade balance position and permanent, namely for the next ten periods. The limitation of this research is that the identification of the existence of the J curve phenomenon is generally carried out on the entire trade balance. Further research is expected to identify the J curve phenomenon specifically in several trading partner countries of Indonesia.